Estudo comparativo entre os parâmetros de força muscular periférica, respiratória e qualidade de vida antes e após o transplante de fígado - Santos, Wedla Lourdes Rebouças Matos Dos (2016)
Liver transplantation is the optimal treatment for acute or chronic, progressive and irreversible liver failure. Metabolic, muscular and respiratory changes resulting from advanced liver disease influence negatively in the functional capacity, generating physical inactivity and impacting functionality and quality of life of patients. This study aimed to evaluate the respiratory muscle strength, peripheral muscle strength, functional capacity and quality of life of patients with terminal chronic liver disease and after liver transplantation. This was a longitudinal, prospective study conducted at the Serviço de Transplante (Liver Transplant Service) of the Walter Cantídio University Hospital (HUWC), from September 2015 to May 2016. 40 patients over 18 years old who had no limiting factors to the data collection procedure were included in the waiting list for liver transplantation.Patients underwent reviews of Six Minute Walk Test (6MWT), Maximal Inspiratory Pressure, Maximal Expiratory Pressure (MEP) and Peripheral Muscle Strength, and respond to the Quality of Life Questionnaire SF-36 in the preoperative, 30 and 90 days post-transplant periods.The work was approved by the Research Ethics Committee of HUWC. The sample had a mean age of 53 ± 11 years, and 62.5% were male (n = 25). In the analysis of functional capacity was a significant improvement over the study period, preoperative (317 ± 217m), 30 days (344 ± 219m) and 90 days post-liver transplantation, (429 ± 171m). In the evaluation of MIP and MEP there was a significant improvement in the 90 days period (MIP = -151.90 ± 76.70 cmH2O and MEP = 93.02 ± 40.77 cm H 2 O) when compared to the preoperative period (MIP = -109.00 -78.25 ± cmH2O and MEP = 70.22 ± 31.89 cm H 2 O) (p <0.05).In peripheral strength evaluation there was no statistically significant difference between the pre- (27.5 kgf) and post liver transplant (30 days 24.4 kgf and 90 days 29.0 kgf) periods.Regarding quality of life, patients had higher scores in the questionnaire used in all areas at 90 days post-liver transplantation period , compared to the preoperative period scores. We conclude that in the sample, there was improvement in respiratory muscle strength, functional capacity and quality of life in patients with chronic liver disease after 90 days of terminal liver transplant, without changing the peripheral muscle strength.